Analyzing Internal And External Factors Affecting MSME Performance - Muliana; Hikmah (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to analyze the factors that influence the performance of Micro, Small, and Medium Enterprises (MSMEs) in Batam City. MSME performance is a complex function of internal (endogenous) and external (exogenous) pressures, thus requiring a robust analytical framework to measure the relative weight and interaction of these factors. This study uses a survey method as the main approach and a Structural Equation Modeling (SEM) model using SmartPLS on 150 MSME actors in Batam City. The results of convergent validity, discriminant validity, and reliability tests show that all indicators are valid (Outer Loading > 0.7; AVE > 0.5) and reliable (Composite Reliability > 0.6; Cronbach's Alpha > 0.7). The main findings indicate that external factors have a positive and significant effect on internal factors (Path Coeff. 0.328;. P-value 0,000), external factors have a positive and significant effect on MSME performance (Path Coeff. 0.232; P-value 0.025), and internal factors have a positive and significant effect on MSME performance (Path Coeff. 0.253; P-value 0.042). The F-square value indicates that the contribution of these effects falls into the moderate to strong category. In general, all research hypotheses are accepted, confirming that both external and internal factors play an important role in improving the performance of MSMEs in Batam City.